Development and Validation of a Chemistry Laboratory Safety Knowledge, Attitudes, Practices, and Mindset Questionnaire - Garcia, Claudine (Archīum Ateneo, 2024)
Accidents in chemistry laboratories can be prevented by fostering a safety culture - the institution’s knowledge, attitudes, practices (KAP), and mindset regarding laboratory safety. To effectively promote a safety culture, robust tools are essential for evaluating safety KAP and mindset. Hence, this study developed and validated a questionnaire that can rapidly measure laboratory safety KAP and mindset to guide targeted interventions aimed at enhancing the safety culture in chemistry laboratories. The study was drawn from existing validated questionnaires in constructing a tool comprising 40 items that can measure the safety KAP and mindset in chemistry laboratories. Using a cross-sectional design, the developed questionnaire was administered to undergraduate students taking General Chemistry Laboratory for initial testing, and the revised questionnaire was administered to undergraduate students enrolled in the Principles of Chemistry Laboratory, Organic Chemistry Laboratory, or Physical Chemistry Laboratory for re-testing. The safety knowledge items underwent item analysis by computing their discrimination indices, whereas the safety attitudes, practices, and mindset items were subjected to factor analysis and reliability testing. After this series of analyses, the remaining 12 items demonstrated high validity and reliability in rapidly measuring the safety KAP and mindset in chemistry laboratories. This rapid questionnaire can provide a valuable resource for assessing and improving the safety culture in chemistry laboratories.